OUTCOME OF TEMPOROMANDIBULAR JOINT ARTHROPLASTY WITH TEMPORALIS FSCIA INTERPOSITION - Sajjad Ahmed; Riaz Ahmed Warriach; Muhammad Arshad Badar (Journal of University Medical & Dental College, 2014)
ABSTRACT: OBJECTIVE: To assess the outcomes of temporomandibular joint arthroplasty with temporalis fascia interposition. METHODOLOGY: This is a prospective study carried out over a period of 1 year and twenty days on 65 patients reporting to the department of Oral & Maxillofacial Surgery, Mayo Hospital of Lahore. Jaw ankylosis was diagnosed by clinical as well as radiographic aids. A preauricular incision was given to expose the ankylosis. The ankylosis was released by creating a gap of 1cm between the temporal bone and mandibular condyle. Temporalis fascia flap was raised and interposed in the gap created between temporal bone and mandibular condyle and secured with vicryl sutures to the medial tissues. Interincisal distance was measured by using a ruler. The drain was secured and the incision was closed in layers. After surgery all the patients were kept under observation in the ward for 5-7 days till the removal of sutures and drains. Meanwhile jaw exercise was advised. Patients were followed after seven days, one month and six months postoperatively. RESULTS: The study included; 40 (61.53%) males and 25 (38.46%) females giving a male to female ratio of 8:5. Out of total 65 patients 59 (90.76%) had the history of trauma and only 6 (9.23%) gave the history of infection/disease in early childhood. Patients were operated to treat ankylosis by removal of the ankylotic mass and interposition of temporal fascia. The final assessment of all the patients revealed that 4 patients (6.15%) had mouth opening in the range of 40-50 mm, while 41 patients (63.07%) had mouth opening in the range of 35-39 mm. CONCLUSION: The results of this study shows that temporomandibular joint ankylosis can be managed effectively with the arthroplasty of the affected joint and interposition of temporalis fascia in the newly created joint space.